Producing Home Grown Solutions : Think Tanks and Knowledge Networks in International Development - Datta, Ajoy (2012)
Mainstream international development discourse has long heralded the importance of home grown solutions and national ownership of development policies. Ownership has been seen as the missing link between the significant development aid inflows from the North and poverty reduction outcomes in the South. You only have to look to international agreements such the 2002 Monterrey Consensus or the2005 Paris Declaration for evidence of this.